Comparing social stigma of anorexia nervosa, bulimia nervosa, and binge-eating disorder: A quantitative experimental study - Carlye S. Aird; Bennett A. A. Reisinger; Stephanie N. Webb; David H. Gleaves (Journal of Eating Disorders)
Abstract Background Currently, we know little regarding how stigma attributed to eating disorders compares to that of other psychological disorders and additionally within different types of eating disorders. In the current study, we aimed to explore the stigmatisation of eating disorders by comparing the stigma attributed to anorexia nervosa, bulimia nervosa, and binge-eating disorder, utilising depression as a comparative control. Methods A total of 235 participants from the general population were randomly assigned to an anorexia nervosa, bulimia nervosa, binge-eating disorder, or depression condition. Participants responded to a questionnaire consisting of several adapted versions of pre-existing subscales that measured levels of stigma associated with psychological disorders generally, as well as stigma associated with eating disorders specifically. We used several one-way analyses of variance to investigate the differences in stigma attributed towards the aforementioned psychological disorders. Results Results suggested that all three eating disorders were significantly more stigmatised than was depression. Between the eating disorders, the three were generally equivalent except that binge-eating disorder was significantly more stigmatised than both anorexia nervosa and bulimia nervosa on a subscale measuring trivialness. Conclusions These findings indicate that individuals with eating disorders, including binge-eating disorder, may be at a higher risk of experiencing the negative implications of stigma when compared to other psychological disorders, such as depression. To our knowledge, this study is one of few that directly quantify and compare stigma attributed towards anorexia nervosa, bulimia nervosa, and binge-eating disorder. Through further research, a better understanding around the expression of stigma towards specific eating disorders could inform the development of targeted interventions to help reduce the stigma associated with these disorders. This knowledge could also advance the understanding of the lived experience of individuals living with eating disorders, subsequently informing treatment practices.